Drawn to New York an illustrated chronicle of three decades in New York City - Kuper, Peter 1958- (PM Press, 2013)
With comics, illustrations, and sketches, this work of art portrays everything from the low life to the high energy that has long made people from around the world flock to the Big Apple
Keywords: Kuper, Peter -- 1958-; New York -- NY, Motiv; Graphic Novel; Kuper, Peter / 1958-; New York (N.Y.) / Comic books, strips, etc; Caricatures and cartoons; American wit and humor, Pictorial; City and town life / New York (State) / New York / Humor; City and town life; New York (State) / New York; Graphic novels; Comics (Graphic works); Comic books, strips, etc; Humor; Comic